Aprendiendo a ser un papá: ¿Cómo se hace? ¿No hay un manual en algún lugar? - Kate Fogarty; Garret D. Evans (EDIS, 2011)
Learning to be a good father isn’t for flojos. This 5-page Spanish-language fact sheet was written by Kate Fogarty and Garret D. Evans and published by the UF Department of Family Youth and Community Sciences, May 2011.